2021
DOI: 10.31219/osf.io/9p6jx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Studies on the COVID-19 pandemic in Bosnia-Herzegovina

Abstract: Not applicable, this preprint is a letter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Another example includes Türkiye donating 30 thousand doses of Sinovac vaccines against coronavirus (COVID-19), raising praise from Bosniak state representatives. "Türkiye showed that she is ready to support us like always," said Bosnia-Herzegovina Minister of Security Cikotić (Türkiye Stops COVID 2020).…”
Section: Public Diplomacy: Education Religion and Cultural Heritagementioning
confidence: 99%
“…Another example includes Türkiye donating 30 thousand doses of Sinovac vaccines against coronavirus (COVID-19), raising praise from Bosniak state representatives. "Türkiye showed that she is ready to support us like always," said Bosnia-Herzegovina Minister of Security Cikotić (Türkiye Stops COVID 2020).…”
Section: Public Diplomacy: Education Religion and Cultural Heritagementioning
confidence: 99%